2020
DOI: 10.1038/s41419-020-02947-3
|View full text |Cite
|
Sign up to set email alerts
|

PKC-δ deficiency in B cells displays osteopenia accompanied with upregulation of RANKL expression and osteoclast–osteoblast uncoupling

Abstract: PKC-δ is an important molecule for B-cell proliferation and tolerance. B cells have long been recognized to play a part in osteoimmunology and pathological bone loss. However, the role of B cells with PKC-δ deficiency in bone homeostasis and the underlying mechanisms are unknown. We generated mice with PKC-δ deletion selectively in B cells by crossing PKC-δ-loxP mice with CD19-Cre mice. We studied their bone phenotype using micro-CT and histology. Next, immune organs were obtained and analyzed. Western blottin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…The serum levels of amino-terminal propeptide of type 1 procollagen (P1NP), type 1 collagen C-terminal telopeptide (CTX-1), and interferon-gamma (IFN- γ ) were measured by ELISA kits (Elabscience, Wuhan, China) according to the manufacturer's instructions. The intra-assay and interassay coefficients of variation were below 6.5% and 7.0% for P1NP [ 31 ], 5.5% and 6.0% for CTX-1 [ 32 ], and 6.5% and 7.0% for IFN- γ [ 33 ]. Quantification was measured using a microplate reader (Thermo Fisher Scientific, Waltham, USA) at 450 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The serum levels of amino-terminal propeptide of type 1 procollagen (P1NP), type 1 collagen C-terminal telopeptide (CTX-1), and interferon-gamma (IFN- γ ) were measured by ELISA kits (Elabscience, Wuhan, China) according to the manufacturer's instructions. The intra-assay and interassay coefficients of variation were below 6.5% and 7.0% for P1NP [ 31 ], 5.5% and 6.0% for CTX-1 [ 32 ], and 6.5% and 7.0% for IFN- γ [ 33 ]. Quantification was measured using a microplate reader (Thermo Fisher Scientific, Waltham, USA) at 450 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Emerging evidence highlights the potential of B cells in osteo-immunological regulation that is further supported by the physiological and anatomical coexistence of B cells and bone cells in BM. 121 Recently, several findings suggested that B cells are the active modulator of the RANKL/OPG axis and the production of RANKL by B cells further augmented bone loss in ovariectomy induced bone loss. 122 Interestingly, a report suggested that along with enhancing the OCs differentiation RANKL also increases B cell number that further acts as an OCs supporter cell.…”
Section: Adaptive Immune Cells and Osteoporosismentioning
confidence: 99%
“…Prkcd fl/fl mice on the B6 background were developed by Drs. Niino, Shioda and Sakimura (Li et al, 2020) and purchased from the RIKEN BioResource Center (RBRC06462). Mice were immunized i.p.…”
Section: Mice and Immunizationsmentioning
confidence: 99%